Hubungan antara pengasuhan orangtua dengan masalah makan pada anak usia prasekolah - Riswan, Riswan; Yunitasari, Eva (Utan Kayu Publishing, 2020)
Parenting is very important in the child’s psychological growth and development, the child’s ability to socialize, children’s independence, and difficult eating behavior in children. Because of the phenomenon that often arises is the child has difficult eating which is influenced by parenting parents. This research objective was to determine the correlation between parenting parents with difficult eating behavior on children’s pre-school age at the Sindang Garut village of Way Lima sub-district in Pesawaran Regency. This research was quantitative type with cross sectional approach to the sampling technique used is purposive sampling. The sample were 30 respondents. Data collection used questionnaire sheets and it used gamma statistical tests. The results showed that parenting parents applied were democratic parenting (56.7 percent), and difficult eating behavior in children’s pre-school age at the Sindang Garut village with low intensity (73.3 percent) with p value of 0.006 less than 0.05, which means there is a correlation between parenting parents with difficult eating behavior in children’s pre-school age at the Sindang Garut village of Way Lima sub-district in Pesawaran Regency. So this research is expected to be a source of reference and information for parents about the importance of parenting because it can influence the behavior of eating difficulties on children. Abstrak: Pola asuh orang tua sangat penting dalam tumbuh kembang anak dalam psikologis anak, kemampuan bersosialisasi anak, kemandirian anak, serta perilaku sulit makan pada anak. Karna fenomema yang sering muncul adalah anak mengalami sulit makan yang dipengaruhi oleh pola asuh orang tua. Penelitian ini bertujuan untuk mengetahui hubungan pola asuh orang tua dengan perilaku sulit makan pada anak usia prasekolah di desa sindang garut kecamatan way lima kabupaten pesawaran. Penelitian ini merupakan jenis peneltian kuantitatif dengan pendekatan Cross Sectional teknik pengambilan sampel yang digunakan adalah purposive sampling. dengan jumlah sampel 30 responden. Pengumpulan data menggunakan lembar kuesioner dan uji statistik gamma. Hasil penelitian menunjukan mayoritas pola asuh yang diterapkan adalah pola asuh demokratis (56,7 persen), dan perilaku sulit makan pada anak di desa sindang garut dengan intensitas rendah (46,7 persen) dengan nilai p value 0,006 kurang dari 0,05, yang artinya ada hubungan pola asuh orang tua dengan perilaku sulit makan pada anak usia prasekolah di desa sindang garut kecamatan way lima kabupaten pesawaran. Maka penelitian ini diharapkan bagi orang tua agar dapat menerapkan pola asuh demokratis sehingga dapat mengurangi kejadian sulit makan pada anak usia prasekolah.